2006
DOI: 10.4049/jimmunol.176.8.4590
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of CD38 Accelerates Autoimmune Diabetes in NOD/Lt Mice by Enhancing Autoimmunity in an ADP-Ribosyltransferase 2-Dependent Fashion

Abstract: Ubiquitously expressed CD38 and T cell-expressed ADP-ribosyltransferase 2 (ART2) are ectoenzymes competing for NAD substrate. CD38 exerts pleiotropic actions in hemopoietic and nonhemopoietic compartments via effects on calcium mobilization. ART2 is an ADP-ribosyltransferase on naive CD4+ and CD8+ T cells. ART2-catalyzed ADP-ribosylation of the P2X7 purinoreceptor elicits apoptosis. Transfer of a genetically disrupted CD38 allele into the autoimmune diabetes-prone NOD/Lt background accelerated diabetes onset i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
80
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 57 publications
9
80
0
Order By: Relevance
“…It is likely that the mechanisms described in this study with mechanically disrupted erythrocytes act also in these and other settings in vivo. Indeed, recent results from three different mouse models of inflammation support the notion that nucleotides released during tissue injury induce P2X 7 activation on T cells in vivo (6,18,25). Firstly, injection of Con A induces T cell-dependent hepatitis that is accompanied by fulminant liver cell damage as evidenced by the release of cytosolic enzymes into the circulation.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…It is likely that the mechanisms described in this study with mechanically disrupted erythrocytes act also in these and other settings in vivo. Indeed, recent results from three different mouse models of inflammation support the notion that nucleotides released during tissue injury induce P2X 7 activation on T cells in vivo (6,18,25). Firstly, injection of Con A induces T cell-dependent hepatitis that is accompanied by fulminant liver cell damage as evidenced by the release of cytosolic enzymes into the circulation.…”
Section: Discussionmentioning
confidence: 87%
“…Secondly, genetic ablation of the major ecto-NADglycohydrolase CD38 results in elevated tissue NAD levels and enhanced levels of T cell surface ADP-ribosylation (24). Transfer of the deficient CD38 allele into the autoimmune diabetesprone NOD/Lt background resulted in accelerated disease progression, correlating with an enhanced sensitivity of regulatory T cells to ART2-dependent NAD-induced cell death in these mice (25). Indeed, these changes were corrected when CD38 deficiency was combined with ART2 deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others did not observe a significant defect in glucose tolerance in Cd38 Ϫ/Ϫ mice on the C57BL/6 genetic background (58). It is possible that genetics could account for the differences in whole-body glucose metabolism.…”
Section: Our Finding Of Normoglycemia In Cd38mentioning
confidence: 97%
“…Interestingly, cytokines responsible for ␤-cell apoptosis in type 1 diabetes, namely tumor necrosis factor ␣, interleukin-1␤, and interferon ␥, have all been shown to alter CD38 expression in other cells types (65,66). While this report was in revision, Leiter et al (58) reported that CD38 deficiency significantly accelerated diabetes in NOD mice. While the CD38 Ϫ/Ϫ : NOD study focused largely on the roles of CD38 in the immune system, their results also pointed to effects in nonhematopoietic cells (58).…”
Section: Our Finding Of Normoglycemia In Cd38mentioning
confidence: 99%